The Concept of Happiness from the Perspective of the Qur'an: A Thematic Analysis of the Verses of the Blessings of Heaven as a Reflection on Achieving Happiness in the World - Darmawan Darmawan; Kusnadi Kusnadi; Aristophan Firdaus (Penerbit Hellow Pustaka, 2026)
Descriptions of the blessings of paradise are widely mentioned in the Qur’an in various forms, yet they are commonly understood merely as eschatological rewards in the hereafter. However, upon deeper examination, these descriptions are not only informative, but also contain moral and spiritual values that can be reflected as a foundation for happiness in worldly life. This study aims to identify Qur’anic verses that depict the blessings of paradise and explain how these descriptions can be reflected as a Qur’anic concept of happiness for human life in the world. This research employs a qualitative method through library research by examining tafsir works and relevant literature, collecting verses related to paradise, analyzing their meanings, and formulating the characteristics of paradise’s blessings—both material and spiritual. The findings reveal that the blessings of paradise are not only eschatological rewards, but also contain moral and spiritual messages that may serve as a guide for achieving true happiness in the world. Thus, the Qur’anic portrayal of paradise can be understood as an ideal model of happiness based on faith, inner peace, and noble character.